Evidence for the presence of active paraoxonase 1 in small-dense low-density lipoprotein. (28th May 2014) - Gugliucci, Alejandro; Caccavello, Russell; Kotani, Kazuhiko; Kimura, Satoshi
Abstract : Aim: We have recently demonstrated the quick ex vivo transfer of paraoxonase 1 (PON1) activity from high-density lipoprotein (HDL) to small, dense low-density lipoprotein (sdLDL). We set out to assess whether sdLDL contains active PON1 in vivo . Methods: We conducted a nested case–control, proof of principle study with the Japanese healthy subjects with normal lipids ( n  = 23) and age and gender-paired dyslipidemic subjects ( n  = 17). Lipid panels, lactonase and arylesterase assays, and PON1 zymogram in the LDL and HDL subclasses were assessed. Results: PON1 specific activity in the high-molecular weight lipoprotein fraction corresponding to LDL migration was found in 48% of normo and in 29% of dyslipidemic Japanese subjects. This band co-localizes with apoB100 and not Lp(a) and displays a lower molecular mass than the bulk of LDL. Conclusion: We provide evidence, for the first time, that native sdLDL contains up to 4% of the total PON1 activity in the serum of up to 48% of the Japanese subjects. Could the PON1-containing sdLDL represent a set of particles with a defense mechanism from oxidation and therefore its levels actually prove to be atheroprotective? If further studies confirm this contention, a zymogram of PON1 in LDL subclasses could be a functional assay that complements the current methods that only inform on the size and lipid concentration of these particles.